Explanatory styles of professional football coaches in the analysis of sports competition - Ortín, Francisco José; Ortega, Enrique; López, Elena; Olmedilla, Aurelio (Anales de Psicología / Annals of Psychology, 2012)
The aim of this research was analyzing the explanatory styles of professional coaches at the end of competition matches. We collected 4366 coaches ́ declarations in the press belonging to 29 league season fixtures, which are related to the dimensions of the explanatory styles theory and aspects like result, place, stage of the season and category. The results show significant differences in the three dimensions of the explanatory guidelines respected to the analyzed aspects. We discuss the importance of the explanatory styles of coaches to influence on the team performance, as well as the possible difference of attributing according to what was analyzed and the possibilities of psychological counselling to coaches in order to improve the performance evaluation and the feedback to football players.